Association of Cognitive Impairment, Depression, Supportive Social Networks, Fear and Death Anxiety in Older Adults - Figueroa Varela, Ma. del Rocío (Consorcio de Universidades Mexicanas A.C., 2021)
Aging implies a very important change followed by loss of functional and neuropsychological abilities, as well as significant processes like coping of death. It is important to study the way older adults deal with the meaning of death and anxiety generated. Through a cross-sectional, correlational study, the Folstein Mini Mental, Yesavage Scale, Templer’s Fear of Death, Collet Lester’s Death Anxiety and a supportive social network questionnaire were applied in a non-probabilistic sample of 63 older adults who attend to institutional support groups. The results indicate cognitive impairment prevalence of 9.5%, reporting depression especially in women (17%). There is an association between continuing working and fear of death, as well as anxiety about death and having chronic-degenerative disease, there is also a correlation between depression and fear at the end of the life, the process and occurrence of the death of a relative, which is the highest indicators of anxiety. The results are discussed in relation to some aspects of gender, support of the family and social support network, as well as access to health and social security services.